Optogenetic Stimulation of Gi Signaling Enables Instantaneous Modulation of Cardiomyocyte Pacemaking - Cokić, Milan; Bruegmann, Tobias; Sasse, Philipp; Malan, Daniela (Frontiers in Physiology, 2021)
G-protein signaling pathways are central in the regulation of cardiac function in physiological and pathophysiological conditions. Their functional analysis through optogenetic techniques with selective expression of opsin proteins and activation by specific wavelengths allows high spatial and temporal precision. Here we present the application of long wavelength-sensitive cone opsin (LWO) in cardiomyocytes for activation of the Gi signaling pathway by red light. Murine embryonic stem cells expressing LWO were generated and differentiated into beating cardiomyocytes in embryoid bodies. Illumination with red light (625 nm) led to an instantaneous decrease up to complete inhibition (84-99% effectivity) of spontaneous beating, but had no effect on control embryoid bodies. By using increasing light intensities with 10 s pulses, we determined a half maximal effective light intensity of 2.4 µW/mm2 and a maximum effect at 100 µW/mm2. Pre-incubation of LWO embryoid bodies with pertussis toxin completely inhibited the light effect proving the specificity for Gi signaling. Frequency reduction was mainly due to activation of GIRK channels because the specific channel blocker tertiapin reduced the light effect by ~80%. Compared to pharmacological stimulation of M2 receptors with carbachol with slow kinetics (> 30 s), illumination of LWO had an identical efficacy, but much faster kinetics (< 1 s) in activation and deactivation demonstrating the temporal advantage of optogenetic stimulation. Thus, LWO is an effective optogenetic tool for selective stimulation of the Gi signaling cascade in cardiomyocytes with red light, providing high temporal precision.